Insights into the surface property and blood compatibility of polyethersulfone/polyvinylpyrrolidone composite membranes: toward high‐performance hemodialyzer. (29th May 2014) - Qin, Hui; Nie, Shengqiang; Cheng, Chong; Ran, Fen; He, Chao; Ma, Lang; Yin, Zehua; Zhao, Changsheng
<x xml:space="preserve">Abstract</x> Applications of blood purification membranes are fuelled by diverse clinical needs, such as hemodialysis, hemodiafiltration, hemofiltration, plasmapheresis, and plasma collection. For clinical usage, the adding of polyvinylpyrrolidone (PVP) is the general protocol for the design of antifouling and antithrombotic properties integrated artificial membranes. In the present work, to insight into the detailed surface properties and blood compatibilities of the PVP blended composite membranes, we synthesized a series of PVP polymers with different molecular weights using reversible addition fragmentation chain transfer polymerization and designed a series of polyethersulfone (PES)/PVP composite membranes by a physically blending method. The effects of PVP molecular weights and blending ratios on the surface properties and the blood compatibilities of the composite membranes were investigated in detail. The surface attenuated total reflection Fourier transform infrared spectra and scanning electron microscopy pictures indicated that the PVP was successfully immobilized into the membranes, and the composite membranes exhibited morphology transformation from finger‐like structure to sponge‐like structure, which indicated that the composite membrane had tunable porosity and permeability by adding PVP. The blood compatible tests revealed that the composite membranes showed increased hydrophilicity, decreased plasma protein adsorption, suppressed platelet adhesion, and prolonged blood clotting time compared with pristine PES membrane. These results indicated that the PES/PVP composite membranes exhibited enhanced antifouling and antithrombotic properties than the pristine PES membrane. Meanwhile, the results also suggested that the composite membranes with larger molecular weight PVP and higher blending ratios might show better blood compatibility. Copyright © 2014 John Wiley & Sons, Ltd.